Natural polyphenols may ameliorate damage induced by copper overload - Arnal, Nathalie (2012)
The effect of the simultaneous exposure to transition metals and natural antioxidants frequently present in food is a question that needs further investigation. We aimed to explore the possible use of the natural polyphenols caffeic acid (CA), resveratrol (RES) and curcumin (CUR) to prevent damages induced by copper-overload on cellular molecules in HepG2 and A-549 human cells in culture. Exposure to 100 μM/24. h copper (Cu) caused extensive pro-oxidative damage evidenced by increased TBARS, protein carbonyls and nitrite productions in both cell types. Damage was aggravated by simultaneous incubation with 100 μM of CA or RES, and it was also reflected in a decrease on cellular viability explored by trypan blue dye exclusion test and LDH leakage. Co-incubation with CUR produced opposite effects demonstrating a protective action which restored the level of biomarkers and cellular viability almost to control values. Thus, while CA and RES might aggravate the oxidative/nitrative damage of Cu, CUR should be considered as a putative protective agent. These results could stimulate further research on the possible use of natural polyphenols as neutralizing substances against the transition metal over-exposure in specific populations such as professional agrochemical sprayers and women using Cu-intrauterine devices.